Maternal age and outcome of preterm infants at discharge from the neonatal intensive care unit. Issue 2 (February 2016) - Eventov-Friedman, Smadar; Zisk-Rony, Rachel Y.; Nosko, Sophia; Bar-Oz, Benjamin
Abstract: Objective: To assess the effect of maternal age on preterm neonates' survival free from major morbidity at discharge from two neonatal intensive care units in Jerusalem, Israel. Methods: A retrospective chart review of two hospitals from 2009–2010 was performed. Eligible neonates were born at less than 35 weeks of gestation and survived to discharge. Major morbidity included at least one of the following: chronic lung disease, at least grade 3 intraventricular hemorrhage, periventricular leukomalacia, at least stage 3 retinopathy of prematurity, at least stage 2 necrotizing enterocolitis, or sepsis. Results: The analysis was performed on 380 neonates of 294 mothers. Mean maternal age was 30.5 years (range, 17–52), mean gestational age was 31.5 weeks (range, 24–34), and mean birth weight was 1705.5 g (range, 460–3150). Of the neonates, 90 (23.7%) had major morbidity, which was associated with lower mean gestational age (29.5 weeks vs 32.3 weeks, P < 0.001), birth weight (1326.5 g vs 1822.2 g, P < 0.001), and the need for resuscitation at birth ( P < 0.001) in comparison with neonates without major morbidity. A comparison of maternal age between the two outcome groups yielded a nonsignificant result. A logistic regression model revealed that maternal age does not contribute significantly to poor neonatal outcomes. Conclusion: Advanced maternal age was not associated with major morbidity of preterm neonates at discharge from the neonatal intensive care units.